Building physics: lighting : seeing in the artificial environment - Stevens, Wallace Roberts (Commonwealth and international library. Physics division., 1969)
Building Physics: Lighting, Seeing in the Artificial Environment deals with basic principles of lighting as used in architecture, in building maintenance, and in an artificial environment. The book starts with the process of how humans see; the interaction of the eye and mind; and the effects of fatigue, visual disorders, and age. The phenomena of light are then discussed - how light behaves and how it is measured. Light and light waves beyond the visible spectrum are explained scientifically as being part of the electromagnetic spectrum within the 400 to 760 nm ranges. The different light so.